2008
DOI: 10.1080/14635240.2008.10708137
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of non-participation in health promotion interventions and its impact on population level outcome

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…23 The King's Fund 24 reported a higher level of dissatisfaction with NHS services amongst ethnic minority groups, but factors such as health and socio-economic deprivation did not fully account for the differences in access to care. A review of adherence to treatment 25 highlights patients' health beliefs as being important in influencing their decisions regarding compliance.…”
Section: Discussionmentioning
confidence: 99%
“…23 The King's Fund 24 reported a higher level of dissatisfaction with NHS services amongst ethnic minority groups, but factors such as health and socio-economic deprivation did not fully account for the differences in access to care. A review of adherence to treatment 25 highlights patients' health beliefs as being important in influencing their decisions regarding compliance.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, CHWs provided toothpaste and toothbrushes free of charge to all members living in an enrolled family's household. Prior studies distributing free oral hygiene supplies have yielded significant improvements in oral health outcomes in the absence of intervention at the level of intensity employed in MSB (e.g., minimal education, counseling, or hygiene instruction; Sgan-Cohen et al 2001;Davies et al 2002;Joury et al 2016;Davies et al 2021). Thus, providing oral hygiene supplies alone may have served to prioritize toothbrushing behaviors in this study, contributing to the positive changes observed.…”
Section: Discussionmentioning
confidence: 71%
“…A reduced number of examined eighteen-year-olds is due to failure to respond to timely dental examination at the health center and/or visit to private dental office. It is possible that the incidence of orthodontic anomalies and caries is much higher among unscreened children of this age [15]. Such high percentage of children with untreated orthodontic problems can be reduced only by improving preventive work at an earlier age [16]; otherwise, the treatment of orthodontic anomalies is going to be more complicated and more expensive.…”
Section: Discussionmentioning
confidence: 99%